Pay, Promotion, Work, Supervision, and Coworker as Dimensions of Academicians Job Satisfaction at Public Research Universities in Klang Valley, Malaysia (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2021)
Recognizing and evaluating effective and principal factors that have been affected by academicians' feelings and satisfaction are imperative. This cross-sectional study aims to examine coworker's influence, pay, promotion, supervision, and work on academicians' job satisfaction at university. Job Descriptive Index (JDI) measured these factors, which comprised 72 items and proposed by Brodke et al. (2009) amongst 440 academicians who worked in public research universities in Klang Valley, Malaysia. Descriptive Statistics analyzed the achieved data.  This study has illustrated that most academicians revealed a high level of satisfaction toward their pay, coworker, promotion, supervision, and work; their universities support them regarding the main factors of work and organizational structure. Based on these consequences, the universities and any other academic institutes have to the consciousness of these five main factors to improve and enhance academicians job satisfaction, leading to high outcomes and performance at the workplace.